The value of religious moderation education in mosques: peace, tolerance, historicity, balance, and contextuality - Mahsun; Lubna Riyu Azharani; Aunillah Ahmad (At Turots: Jurnal Pendidikan Islam, 2025)
This research is based on an interest in seeing tradition as a medium of religious moderation education, where religious moderation is currently seen as one solution to respond to and prevent the phenomenon of anti-human religious practices. The aim is to find out: (1) what is the form of tradition in the Wali Menggoro Mosque and (2) what are the educational values of religious moderation contained in that tradition? This field research is qualitative with a phenomenological approach. Data collection through interviews and observations of visitors, mosque takers (takmir), community leaders, and social situations research. From the results of the research, it is known: (1) the tradition of Menggoro Mosque is a cultural meeting with religious teachings since the era of the early spread of Islam in Temanggung which took the form of a series of Nazar rituals, Kembang Boreh, Mujahadah, Saka Bertuah, Ziarah, and Pasar Malam; (2) the educational values of religious moderation contained in a series of rituals in the Menggoro Mosque tradition consist of the values of peace, tolerance, balance, historicity, and contextuality. The novelty of this study lies in findings about the function of traditions based on historic mosques as a medium of cultivation, practice, and dissemination of the educational value of religious moderation. On a global scale, the results of this research are expected to contribute to global peace education through the media of community traditions to fight and prevent all forms of terrorism, intolerance, extremism, and exclusivism in the name of religion.